Structure analysis and antioxidant activities of an amylopectin-type polysaccharide isolated from dried fruits of Terminalia chebula. (1st May 2019) - Jeong, Hye Kyoung; Lee, Dongjoo; Kim, Hong Pyo; Baek, Seung-Hoon
Graphical abstract: Highlights: A neutral polysaccharide (TFP-a) was isolated from fruits of Terminalia chebula . The backbone of TFP-a was identical to amylopectin. The side chain of TFP-a might be 1, 4-β-galactan substituted with diverse sugars. TFP-a exhibited potent and dose-dependent antioxidant activities. TFP-a is an amylopectin-type polysaccharide in fruits of T. chebula . Abstract: Dried fruits of Terminalia chebula (TF) are used as herbal medicine for diverse symptoms, and their bioactivities are known to involve antioxidant activities. The aim of this study was to elucidate the structure and antioxidant effects of an active TF polysaccharide (TFP). The neutral polysaccharide (named as TFP-a) isolated by ion-exchange chromatography was a homogenous α-Glc-rich polysaccharide (over 70% α-Glc, 534.9 kDa, PDI 1.36) with a porous and flake-like morphology. Linkage and NMR data comprehensively showed that TFP-a was an amylopectin-type polysaccharide with (1→4)-α-Glc( p ) backbone branched at C6/C2. Side chains were composed of (1→4)-β-Gal( p ) substituted with α-Ara( f ), β-GalUA( p ), β-GalUA( p )-Me, and α-Rham( p ). In antioxidant activity assays, TFP-a exhibited potent and concentration-dependent antioxidant effects, including DPPH and superoxide radical scavenging and reducing power. We concluded that TFP-a is an amylopectin-type polysaccharide that may be used as a potential natural antioxidant.